What's the Story With Blue Steak? On the Unexpected Popularity of Blue Foods - Spence, Charles (Frontiers in Psychology, 2021)
Is blue food desirable or disgusting? The answer, it would seem, is both, but it really depends on the food in which the color happens to be present. It turns out that the oft-cited aversive response to blue meat may not even have been scientifically validated, despite the fact that blue food coloring is often added to discombobulate diners. In the case of drinks, however, there has been a recent growth of successful new blue product launches in everything from beer to tea, and from wine to gin, arguing that coloring food products blue is more than simply a contemporary fad. In fact, the current interest in blue food coloring builds on the color's earlier appearance in everything from blue curacao to blue-raspberry candyfloss (cotton candy), and thereafter a number of soft drinks. Over the years, the combination of blue coloring with raspberry flavoring has also appeared in everything from bubble-gum to patriotic pop rocks (popping candy in The United States). Ultimately, it is the rarity of naturally-blue foods that is likely what makes this color so special. As such, blue food coloring can both work effectively to attract the visual attention of the shopper while, at the same time, being linked to a range of different flavors (since this is one of the few color-flavor mappings that are essentially arbitrary) depending on the food format in which it happens to appear. Note also that the basic descriptor “blue” covers a wide range of hues having a range of different associations, hence eliciting different reactions (be they positive or negative). While blue was once associated with artificiality, a growing number of natural blue food colorings have come onto the market in recent years thus perhaps changing the dominant associations that many consumers may have with this most unusual of food colors.